An ultrasonic method for separation of epiphytic microbes from freshwater submerged macrophytes. (22nd May 2013) - Cai, Xianlei; Gao, Guang; Yang, Jing; Tang, Xiangming; Dai, Jiangyu; Chen, Dan; Song, Yuzhi
Abstract Epiphytic microbes are common inhabitants of freshwater submerged macrophytes, which play an important role in aquatic ecosystems. An important precondition for studying the epiphytic microbes is having an effective method of separating the attached microbes from the host macrophytes. We developed an ultrasound‐based method for separating epiphytic microbes from freshwater submerged macrophytes, optimized the conditions of ultrasonic separation with an orthogonal experimental design, and compared the optimized ultrasonic method with manual separation. This method can be particularly useful for freshwater submerged macrophytes having a complex morphology.